Building A Strong Brand as An Opportunity to Increase Competitiveness - Alicja Katarzyna KRZEPICKA; Jolanta TARAPATA (Communications of International Proceedings, 2021)
‘Products are made in the factory, but brands are created in the mind’ – Walter Landor, Landor Associates. Today the brand is one of the most important instruments of competitive struggle. The brand is not only an intangible resource, but also a resource that is definitely permanent, with a high economic potential.  Building a strong brand is a complex and long-term process, requiring the necessary preparation of strategic foundations and then undertaking tactical activities related to brand creation. Building a brand is a process that requires a diligent and deliberate commitment. In order for this process to help companies in their efforts to increase competitiveness, a comprehensive action plan is needed that describes the corporate image, product functionality and brand management concept, which in the long term determines the consumer's choice of the brand. The main determinant of brand development is the availability of information about it, the attractiveness of its presentation, the high level of technology and the possibility of building a system of recommendations and communities around the brand.  A sign of a strong brand is the loyalty of customers to the brand and the community gathered around it (creating fun brand clubs). By building a strong brand, you can multiply the value of the company. The brand does not function only on the label, but in the consciousness of consumers. Its philosophy and a set of associations associated with it determine its strength. The success of a brand will be determined by whether the consumer wants to identify with the philosophy and personality of the brand. The article tries to show that focusing on building a strong brand from the very beginning can become an opportunity for many companies to increase their competitive position. The aim of this article was to present the current state of knowledge about the brand, pointing out its most important attributes in the context of building a strong brand. Moreover, the issue of brand awareness was discussed as a factor determining its strength and competitive advantage.
Keywords: Brand; Strong Brand; Brand Image; Brand Awareness; Competitive Advantage.